Using principal component analysis to explore consumers' perception toward quinoa health and nutritional claims in Gweru, Zimbabwe - Muziri, Tavagwisa; Chaibva, Paul; Chofamba, Anyway; Madanzi, Tendai; Manjeru, Pepukai; Mudada, Nhamo; Manhokwe, Shephard; Mugari, Amiel; Matsvange, Diego; Murewi, Cyril Tapiwa Farai; Mwadzingeni, Liboster; Mugandani, Raymond (Food Science & Nutrition, 2021)
Quinoa is one of the ancestral grains now considered as the “superfoods of the future” due to their characteristics as functional foods with great environmental adaptability. The Zimbabwe Resilience Building Fund has introduced quinoa in Zimbabwe to increase resilience of farming systems in light of environmental shocks. In order to improve adoption of the crop, it is important to understand the combined effects of sociodemographic variables on consumer perceptions of the crop. However, there is limited literature on the combined effects of socio-demographic variables on quinoa health and nutritional benefits in Zimbabwe. In this study, we used principle component analysis to identify consumers' perception about health and nutritional benefits of quinoa in Gweru Urban District, Gweru, Zimbabwe. A questionnaire was designed and applied to 200 participants. However, only 167 forms were valid for analysis. Age, education, and income level are main factors that determine consumer perceptions on health and nutritional claims. The results indicate that quinoa need to be promoted a as a crop that goes beyond food and income security by placing additional emphasis on health and nutritional aspects. This is very insightful in light of the need to improve the uptake of the crop by smallholder farmers in Zimbabwe. However, the use of self-reporting survey method has received criticism for failing to get detailed information on perceptions of individuals. These findings could be handy to promote quinoa as a climate smart crop with additional health and nutritional benefits. This is one of the novel research studies exploring the motives of Zimbabwean consumers towards quinoa as a functional food crop. The work also contributes to knowledge on consumer food preferences.